rac-12,14-Dicyclopropyl-5,8,13,18,21-pentaoxapentacyclo[13.8.0.0(2,11).0(4,9).0(17,22)]tricosa-1(15),2(11),3,9(10),16,22(23)-hexaene - Tafeenko, Viktor A. (International Union of Crystallography, 2011)
The molecule of the title compound, C(24)H(24)O(5), has crystallographic twofold symmetry, with the central O atom lying on the rotation axis. The dihedral angle between the best planes of the benzene rings fused to the oxepine fragment is 38.5 (1)°. The dioxine ring adopts a twist form with the ethylene group C atoms deviating by 0.472 (5) and −0.248 (6) Å from the plane defined by the remaining ring atoms.